Silencing Human Rights: critical engagements with a contested project - Bhambra, Gurminder K.; Shilliam, Robbie (London Palgrave Macmillan, 2009)
This volume presents a range of topical investigations into the human rights field as well as providing an original and provocative investigation of some of the topic through the theoretical lens of 'silence'.
Keywords: Civil & political rights; Ethnic conflict; Human rights